Keanekaragaman Mikoriza Arbuskula (FMA) pada Beberapa Tegakan di Areal Arboretum Universitas Sumatera Utara - Ria Pertiwi Sianturi; Delvian Delvian; Deni Elfiati (Peronema Forestry Science Journal, 2015)
Existence and Status of Arbuscular Mycorrhizae Fungi is affected by biotic and abiotic factor. The goal of this research is to know diversity of Arbuskular Mycorrhiza Underneath of durian (Durio zibethinus), kemiri (Aleurithes moluccana), asam gelugur (Garcinia atroviridis), and karet (Hevea brasiliensis). Soil sample has been taken from Arboretum Universitas Sumatera Utara under of four tree of MPTS. This research use soil separating method to obtain spores and root coloring method to find out root colonization. The obtained an average spore density on kemiri is 42 spores/50 g soil, durian is 42 spores/50 g soil, karet is 50 spores/50 g soil and asam gelugur is 62 spores/50 g soil. The result shows on four tree of MPTS obtained 23 spores types of Glomus and 8 spores types of Acaulospore with colonization percentage of durianis 25,6%, kemiri is 43,86%, Karet is 49,6% and Asam Gelugur is 50,5%. Key word: FMA, durian, kemiri, asam gelugur, karet, arboretum